Learning Anthropology by Teaching Anthropology: A Case Study of Five Service-Learning Classes at Rollins College - Ashley Kistler (The University of Alabama, 2022)
As an anthropologist, I strive to incorporate the principles of engaged ethnographic research into my teaching. This paper presents a case study of five service-learning projects conducted by anthropology students at Rollins College in Winter Park, Florida. I contrast the minimal impact of two unsuccessful projects focused on documenting participants' family lives with the great success of the later projects, in which my students taught anthropology-themed courses to older adult students. These projects were successful because they were mutually beneficial: They helped my students apply their knowledge outside of the classroom while providing opportunities for continuing education for older adults seeking to engage in academic debate. I argue that using the methods of collaborative ethnography can help scholars to design community engagement experiences that are more impactful for students and community partners alike.